2016
DOI: 10.1007/s11325-016-1313-4
|View full text |Cite
|
Sign up to set email alerts
|

Construct validity and factor structure of the Pittsburgh Sleep Quality Index among pregnant women in a Pacific-Northwest cohort

Abstract: Purpose Poor sleep quality during pregnancy is associated with adverse obstetric and neuropsychiatric outcomes. Despite its routine use as a sleep quality assessment scale among men and non-pregnant women, the psychometric properties of the Pittsburgh Sleep Quality Index (PSQI) have not been assessed among US pregnant women. We sought to evaluate the construct validity and factor structure of the PSQI among 1,488 pregnant women. Methods A structured interview was used to collect information about demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
73
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 29 publications
5
73
1
Order By: Relevance
“…A relationship between prenatal depression and sleep quality in pregnant women has previously been demonstrated, showing that higher levels of prenatal depression predicted poorer sleep quality, as depression is one of the main psychological factors contributing to sleep complaints [7,14,34,35]. The association between poor sleep quality and depressed mood has also been shown in epidemiologic studies of sleep in the general population [36], and with postpartum women [37,38].…”
Section: Discussionmentioning
confidence: 92%
“…A relationship between prenatal depression and sleep quality in pregnant women has previously been demonstrated, showing that higher levels of prenatal depression predicted poorer sleep quality, as depression is one of the main psychological factors contributing to sleep complaints [7,14,34,35]. The association between poor sleep quality and depressed mood has also been shown in epidemiologic studies of sleep in the general population [36], and with postpartum women [37,38].…”
Section: Discussionmentioning
confidence: 92%
“…In obstetric cohorts, PSQI was both reliable and accurate (Qiu et al., ), and with good internal consistency (Cronbach's α = 0.73; Skouteris et al., ). In a study comparing sleep quality during second versus third trimester pregnancy, the internal consistency of the PSQI was supported with a Cronbach's α of 0.73 (Ko et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Since PSQI may be comprised of multiple dimensions, a good understanding of its factor structure in patients with OS can benefit further clinical application. The best factor structure of PSQI varies among previous studies (Koh, Lim, Chia, & Lim, ; Qiu et al, ; Raniti, Waloszek, Schwartz, Allen, & Trinder, ; de la Vega et al, ), probably due to divergent diagnosis of the subjects, inconsistent statistical methodology and different country of origin. Many studies supported a two‐factor solution, which can be more representative of the PSQI's scale structure than other models (Guo et al, ; Qiu et al, ).…”
Section: Discussionmentioning
confidence: 88%
“…The best factor structure of PSQI varies among previous studies (Koh, Lim, Chia, & Lim, ; Qiu et al, ; Raniti, Waloszek, Schwartz, Allen, & Trinder, ; de la Vega et al, ), probably due to divergent diagnosis of the subjects, inconsistent statistical methodology and different country of origin. Many studies supported a two‐factor solution, which can be more representative of the PSQI's scale structure than other models (Guo et al, ; Qiu et al, ). Guo et al () investigated the factor structure of the PSQI in a cohort of 631 undergraduate students and reported that a two‐factor model could best fit the data.…”
Section: Discussionmentioning
confidence: 88%